Optimalisasi Platform Multichannel Chat (QISCUS) Untuk Meningkatkan Keunggulan Kompetitif Pemasaran Perusahaan - Erna Murniati; Natasha Nadira Putri (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to determine and analyze the optimization of the multichannel chat platform (qiscus) to increase marketing competitive advantages in companies. The target research object is companies using the platform. This research uses a descriptive method with a qualitative approach with secondary data obtained from the results of collecting reports or documents -documents in the form of books, journals, important documents, or website sources and YouTube videos. Based on the results of reviews from users of the Qiscus platform, this research shows that there are thousands of trusted companies that use the Qiscus platform which has given companies a competitive advantage in competing in an era of increasingly digital progress. fast at the moment. Qiscus is a multichannel chat platform equipped with chatbots and Robolabs whose function is to make it easier for companies to integrate various communication channels such as live chat, WhatsApp, Facebook Messenger, and others on one platform and one user. Overall, the use of Qiscus provides services in creating customer satisfaction which has many benefits for the continuity of the company, including sustainable profitability, increasing long-term retention and consumer loyalty, as well as improving the company's reputation.